Increase in diagnosis of depressive disorders contributes to the increase in antidepressant use in adolescents. (5th April 2018) - Skurtveit, S.; Bramness, J. G.; Hjellvik, V.; Hartz, I.; Nesvåg, R.; Hauge, L. J.; Handal, M.
Abstract : Objective: To study if the observed increase in use of antidepressants (AD) among adolescents may be explained by higher incidence of depressive disorder diagnosis, increasing treatment of other mental disorders or more liberal prescribing practice. Methods: We used three different study populations of girls and boys aged 13–17 years in Norway: 1) individuals who were diagnosed with depressive disorders in primary health care, 2) individuals who were diagnosed with depressive disorders in secondary health care; 3) individuals who were dispensed ADs as recorded in the prescription database. Dataset 2) and 3) were linked. Results: Incidence of depressive disorders increased from 2010 to 2015 both in primary and secondary health care, especially in girls. One in four girls with incident depressive disorders was prescribed ADs and this proportion was stable over time. Among girls treated with ADs the proportion with a diagnosis where AD treatment is indicated increased from 61.1% to 66.0%. Furthermore, the proportion with moderate or severe episodes of major depressive disorders was stable and high, 72.9% in 2014. Conclusion: The only issue studied that could explain increasing AD use in girls was increasing incidence of depressive disorders. Most adolescents with incident diagnosis of depressive disorders were not treated with ADs.